Aligned carbon nanotubes stabilized liquid phase exfoliated graphene hybrid and their polyurethane dielectric elastomers. (23rd March 2016) - Liu, Suting; Sun, Haibin; Ning, Nanying; Zhang, Liqun; Tian, Ming; Zhu, Wenjun; Chan, Tung W.
Abstract: The liquid phase exfoliation (LPE) method, as a cheap, easily scalable, and eco-friendly method, was used to produce defect-free, unoxidized graphene. A surfactant-free technique was used to concentrate the graphene dispersion through stabilization by carbon nanotubes (CNTs) without functionalization. A special kind of aligned CNT bundles, which can be well dissociated into single CNTs in N- methyl-pyrrolidone by sonication, was used and fabricate Gr-CNT hybrid by π - π interaction. A redispersed stable Gr-CNT dispersion at a concentration of 2 mg mL −1 was used for preparing Gr-CNT/thermoplastic polyurethane (TPU) dielectric composite. The results show that the addition of 3.0 vol.% of hybrid improves the dielectric constant of the TPU greatly. As a result, a 10 times increase in electromechanical sensitivity ( β ) at 1000 Hz and 3.4 times increase in actuated strain at a low electric field (7.5 kV/mm) was achieved. The breakdown strengths of the Gr-CNT/TPU composites with 0.25 vol.% and 1.0 vol.% of hybrid are much higher than that of the pure TPU. As a result, the maximum actuated strain increases greatly from 4.8% for the pure TPU to 7% for the composite with 0.25 vol.% of the hybrid. Meanwhile, the energy density increases from 18 kJ/L for the pure TPU to 25 kJ/L and 48 kJ/L for the composites with 0.25 and 1.0 vol.% of hybrid, respectively.